1998
DOI: 10.1093/carcin/19.9.1631
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor-mediated antiestrogenic and antitumorigenic activity of diindolylmethane

Abstract: Phytochemicals such as indole-3-carbinol (I3C) and sulforaphane are components of cruciferous vegetables which exhibit antitumorigenic activity associated with altered carcinogen metabolism and detoxification. Diindolylmethane (DIM) is a major acid-catalyzed metabolite of I3C formed in the gut that binds to the aryl hydrocarbon receptor (AhR) and treatment of MCF-7 human breast cancer cells with 10-50 microM DIM resulted in rapid formation of the nuclear AhR complex and induction of CYP1A1 gene expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
183
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(193 citation statements)
references
References 42 publications
8
183
0
2
Order By: Relevance
“…Acid condensation products of I3C that bind and activate Ahr may also inhibit the transcription of ER-responsive genes by competing for coactivators or increasing ER degradation [81,89]. In contrast, some studies in cell culture [90,91] and animal models [92] have found that acid condensation products of I3C enhance the transcription of ER-responsive genes.…”
Section: Effects Of Indole-3-carbinol On Estrogen Receptor Activitymentioning
confidence: 99%
“…Acid condensation products of I3C that bind and activate Ahr may also inhibit the transcription of ER-responsive genes by competing for coactivators or increasing ER degradation [81,89]. In contrast, some studies in cell culture [90,91] and animal models [92] have found that acid condensation products of I3C enhance the transcription of ER-responsive genes.…”
Section: Effects Of Indole-3-carbinol On Estrogen Receptor Activitymentioning
confidence: 99%
“…DIM is reported to modulate aryl hydrocarbon receptor (AhR), as evidenced in multiple breast cancer cell lines. 31 Aryl hydrocarbon receptor is a ubiquitous cytoplasmic receptor that, when activated and transported to the nucleus, promotes transcription of genes that stimulate the expression of detoxification enzymes, including the phase I cytochrome P450 (CYP) family. Cellular responses to AhR signaling can either promote or diminish inflammation.…”
Section: Initiation Of Breast Tumorsmentioning
confidence: 99%
“…The major active metabolite of I3C, diindolylmethane (DIM), induces expression of GADD45a, a DNA damage-responsive gene and putative tumour suppressor (Carter et al, 2002). Indole-3-carbinol can activate two pathways linked to cancer prevention: (1) aryl hydrocarbon receptor (AhR) signalling (which leads to expression of phase I enzymes (e.g., CYP1A1) via the xenobiotic response element) and (2) antioxidant/electrophilic response element signalling (resulting in expression of phase II detoxifying enzymes: e.g., oxido-reductases and glutathione-S-transferases) (Chen et al, 1998;Hayes and McMahon, 2001;Kwak et al, 2002). Thus, the ability of I3C to induce enzymes that metabolise genotoxic agents may contribute to cancer prevention.…”
mentioning
confidence: 99%